Reforming public service of Republic of Kazakhstan as necessary condition for effective development of national economy - S. S. Dontsov; A. S. Kadyrova; S. A. Rakhimova; A. A. Nurgaliyeva; A. A. Titkov (Омский научный вестник: Серия "Общество. История. Современность")
The article emphasizes the importance of rational reforms of the public service in Kazakhstan for the successful implementation of all major strategic plans and effective development of the national economy as a whole. The need for permanent reform of the public service as an integral part of all administrative and state reforms is stressed. The most important policy documents governing the reform of the public service in the Republic of Kazakhstan are listed. Paragraph 5 of the Kazakhstan-2050 Strategy, «Further strengthening of the statehood and the development of Kazakhstan’s democracy», in which the ways of reforming the national public service are detailed in main areas, is analyzed in sufficient detail. In the Nation’s Plan «100 Concrete Steps to Implement Five Institutional Reforms», the 1st and 5th reforms are considered as they are dedicated to the formation of a professional state apparatus and an accountable state. The strategic development plan of the Republic of Kazakhstan until 2025 is also analyzed from the perspective of reforming the public sector which is considered as the leader of the upcoming changes. Attention is paid to issues related to the creation of a state of law without corruption. Among the main priorities of the implementation of the Strategy are digitalization of the activities of state bodies, increasing the focus on results and interests of citizens, as well as the modernization of consciousness in the public sector. The most important policy documents specifying ways of reforming the public service in Kazakhstan are the President’s Addresses to the people of Kazakhstan, where special importance is attached to increasing the efficiency of public administration, fighting corruption and ensuring the rule of law, creating a state apparatus focused on the needs of citizens